PROCEDURAL JUSTICE, STIGMA TERORIS TERHADAP KOMUNITAS MUSLIM DI AUSTRALIA - Voni Sri Wijayanti (Jurnal Cahaya Mandalika, 2023)
This research examines the stigma of terrorists against the Muslim community in Australia, which often occurs in Muslims as a minority. After all, Australia is known strongly as a secular and multicultural democratic country that has now faced this issue for a long time. The Australian government has done its best to protect its citizens, including Muslims, as part of the social community. In fact, they have also ratified Article 18 of the Universal Declaration of Human Rights, to protect their citizens. In fact, discrimination against Muslims by the majority, especially the Muslim community, is still common. Creating stereotypes about Muslims who are potential terrorists, because of the symbol of Islam and some terrorist attacks there. After the 9/11 terrorist attacks, many western countries strengthened their anti-terror laws. This weakens the protection of Muslim minorities in the West, they are required to abide by procedures while they are also marginalized from the social sphere. So how does this stigma apply to Australia's Muslim minority? How can this situation lead to the marginalization of the Muslim community there? This question will be answered using procedural justice theory, to analyze why most Muslims there feel marginalized by the law and social environment. To provide data in research will use qualitative methods, sources will be obtained from secondary sources such as books, journal articles, and related research.